deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

FinnFoodPics: A database of Finnish snack foods for investigating modern eating behaviors - Arsene Kanyamibwa; Hendrik Hartmann; Daniel Fängström; William Vikatmaa; Beyza Pocan; Emily E. Perszyk; Xue S. Davis; Artemii Nikitin; Patrik Wikman; Tiina Pellinen; Niina E. Kaartinen; Ursula Schwab; et al. (Food Quality and Preference, 2025)

The Spectrum of Peripheral-Vestibular Deficits and Their Change Over Time in CANVAS/RFC1-Related Ataxia Systematic Review and Meta-Analysis of Quantitative Head-Impulse Testing - Maja Szymanska Heydel; Felix Heindl; Annette Hartmann; Max Borsche; Andreas Traschütz; Dominik Straumann; Michael Strupp; Alexander Andrea Tarnutzer (The Cerebellum, 2025)
Cerebellar ataxia, neuropathy, vestibular-areflexia syndrome (CANVAS) has been linked to biallelic intronic repeat-expansions in RFC1 . Video-head-impulse testing (vHIT) offers a quantitative assessment of the angular vestibulo-ocular reflex (aVOR) of all three canals. We evaluated patterns of peripheral-vestibular impairment, its change over time and evaluated correlations with other parameters. PubMed/Embase were searched for articles reporting vHIT in patients with CANVAS/RFC1-related ataxia. A multiple linear-regression model was used to analyse relationships between vHIT-gains and clinical parameters (age, disease duration, sex, biallelic RFC1 expansion). A special focus was put on sequential vHIT in individual patients. 23/64 studies met inclusion criteria; additional 13 studies were identified through reference screening. Twenty-five studies reported individual vHIT-gains and demographic data, suitable for quantitative analysis. Substantial aVOR-gain reductions were found for horizontal (0.32 ± 0.02, n = 146 patients), anterior (0.39 ± 0.03, n = 27) and posterior (0.29 ± 0.03, n = 27) canals. Linear regression showed an association between horizontal vHIT-gains ( n = 146 patients; range of gain: 0-1.3) and disease duration (range: 0–444 months, coef. =-0.0048, p = 0.031) and male sex (coef. =-0.1604, p < 0.001). A decline in horizontal-canal vHIT-gains at least one side over time was noted in 15/21 patients after a mean follow-up time of 33.4 ± 10.7 months. vHIT is a potential biomarker for monitoring progression of CANVAS/RFC1-related ataxia. The significant association between reduced vHIT-gains and disease duration, and their intra-individual decline over time emphasize that impairment of the aVOR reflects the underlying neurodegenerative disease process. Multi-centre prospective studies are needed for systematic early screening and longitudinal validation as outcome for future targeted therapy trials.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Working memory gating in obesity: Insights from a case-control fMRI study - Nadine Herzog; Hendrik Hartmann; Lieneke K. Janssen; Maria Waltmann; Sean J. Fallon; Lorenz Deserno; Annette Horstmann (Appetite, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Self-reported intake of high-fat and high-sugar diet is not associated with cognitive stability and flexibility in healthy men - Hendrik Hartmann; Lieneke K. Janssen; Nadine Herzog; Filip Morys; Daniel Fängström; Sean J. Fallon; Annette Horstmann (Appetite, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A Variation in FGF14 Is Associated with Downbeat Nystagmus in a Genome-Wide Association Study - Michael Strupp; Stephan Maul; Bettina Konte; Annette M. Hartmann; Ina Giegling; Sophia Wollenteit; Katharina Feil; Dan Rujescu (The Cerebellum, 2020)
Downbeat nystagmus (DBN) is a frequent form of acquired persisting central fixation nystagmus, often associated with other cerebellar ocular signs, such as saccadic smooth pursuit or gaze-holding deficits. Despite its distinct clinical features, the underlying etiology of DBN often remains unclear. Therefore, a genome-wide association study (GWAS) was conducted in 106 patients and 2609 healthy controls of European ancestry to identify genetic variants associated with DBN. A genome-wide significant association ( p < 5 × 10 −8 ) with DBN was found for a variation on chromosome 13 located within the fibroblast growth factor 14 gene (FGF14). FGF14 is expressed in Purkinje cells (PCs) and a reduction leads to a decreased spontaneous firing rate and excitability of PCs, compatible with the pathophysiology of DBN. In addition, mutations in the FGF14 gene cause spinocerebellar ataxia type 27. Suggestive associations ( p < 1 × 10 −05 ) could be detected for 15 additional LD-independent loci, one of which is also located in the FGF14 gene. An association of a region containing the dihydrofolate reductase (DHFR) and MutS Homolog 3 (MSH3) genes on chromosome 5 was slightly below the genome-wide significance threshold. DHFR is relevant for neuronal regulation, and a dysfunction is known to induce cerebellar damage. Among the remaining twelve suggestive associations, four genes (MAST4, TPPP, FTMT, and IDS) seem to be involved in cerebral pathological processes. Thus, this GWAS analysis has identified a potential genetic contribution to idiopathic DBN, including suggestive associations to several genes involved in postulated pathological mechanisms of DBN (i.e., impaired function of cerebellar PCs).

Impact of COMT genotype on serotonin-1A receptor binding investigated with PET - Pia Baldinger; Andreas Hahn; Markus Mitterhauser; Georg S. Kranz; Marion Friedl; Wolfgang Wadsak; Christoph Kraus; Johanna Ungersböck; Annette Hartmann; Ina Giegling; Dan Rujescu; Siegfried Kasper; et al. (Brain Structure and Function, 2014)

Lack of association between 71 variations located in candidate genes and response to acute haloperidol treatment - Ina Giegling; Antonio Drago; Martin Schäfer; Annette M. Hartmann; Thomas Sander; Mohammad Reza Toliat; Hans-Jürgen Möller; Diana De Ronchi; Hans H. Stassen; Dan Rujescu; Alessandro Serretti (Psychopharmacology, 2011)